Productivity of Singapore's Manufacturing Sector: An Industry-Level Non-Parametric Study - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 1998)
A paper seeks to measure and to explain the productivity of Singapore's manufacturing sector using industry level data. It utilizes a non-parametric approach consisting of a set of production distance functions, each of which is obtained by solving a linear programming problem. From a time- series of 1983 to 1993, across 30 industries, 3 indices are obtained: 1. a Malmquist total factor productivity index, 2. an efficiency change index, and 3. a technological change index. The resulting TFP growth stands at 4.6% per annum, considerably greater than previous estimates using aggregate country level data. Three-stage least squares are then applied to the pooled data. Foreign ownership and labor quality are found to have important impact on TFP growth.